2021
DOI: 10.1111/ajt.16446
|View full text |Cite
|
Sign up to set email alerts
|

Spanish experience with heart transplants from controlled donation after the circulatory determination of death using thoraco-abdominal normothermic regional perfusion and cold storage

Abstract: Heart transplantation from controlled donation after the circulatory determination of death (cDCDD) may help to increase the availability of hearts for transplantation. During 2020, four heart transplants were performed at three different Spanish hospitals based on the use of thoraco‐abdominal normothermic regional perfusion (TA‐NRP) followed by cold storage (CS). All donors were young adults <45 years. The functional warms ischemic time ranged from 8 to 16 minutes. In all cases, the heart recovered sinus rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…Besides the improvement of outcomes in cDCDD kidney—and liver—transplantation, NRP makes heart transplantation from cDCDD donors possible, 37 even without the additional need for ex situ machine perfusion as made evident by some recent reports 38‐42 . NRP is also consistent with the successful recovery of lungs for transplantation, as derived from our data (almost 14% of kidneys in the NRP group were obtained from donors who also donated lungs) and as supported by some published experiences 32,43,44 …”
Section: Discussionsupporting
confidence: 86%
“…Besides the improvement of outcomes in cDCDD kidney—and liver—transplantation, NRP makes heart transplantation from cDCDD donors possible, 37 even without the additional need for ex situ machine perfusion as made evident by some recent reports 38‐42 . NRP is also consistent with the successful recovery of lungs for transplantation, as derived from our data (almost 14% of kidneys in the NRP group were obtained from donors who also donated lungs) and as supported by some published experiences 32,43,44 …”
Section: Discussionsupporting
confidence: 86%
“…TA-NRP is being used in the UK, Belgium, and more recently in Spain as a strategy to allow the validation and preservation of hearts of cDCDD donors [63,[83][84][85][86]. In the British experience, most hearts recovered by using TA-NRP have been followed by ex situ machine perfusion.…”
Section: Results Of Transplants From Cdcdd Donors Subject To Nrpmentioning
confidence: 99%
“…In the Papworth technique, TA-NRP is followed by instrumentation on the OCS ™ -Heart device for transportation [82]. Successes with the TA-NRP technique followed by cold preservation and storage for transport have recently been reported by two teams in Belgium (Liège, Leuven) [83,84] and three centers in Spain [85,86].…”
Section: Thoraco-abdominal Nrpmentioning
confidence: 99%
“…We have demonstrated that TA‐NRP DCD organ procurements meet the ethical standards of informed consent/authorization, non‐maleficence, adherence to the dead donor rule and irreversibility so they are, at minimum, ethically acceptable. If TA‐NRP DCD donation provides an opportunity for the procurement of more, and possibly, better quality donor organs, then the benefit of this type of organ donation is greater and TA‐NRP DCD has the possibility of enhancing the benefit of more lives saved from organ donation 17,18 …”
Section: Does Normothermic Regional Perfusion Meet the Ethical Standa...mentioning
confidence: 99%